Intuitive Intelligence for teams and organisations - Subiah, Manj (Henry Stewart Talks, 2020)
Strategy, power decision making paradigm, Organisational structure, Intuitive intelligence for teams in the organisation, Organisational cultural behavioural context, Resources and capabilities in the organisation